PENTINGNYA SARAPAN PAGI DALAM MENUNJANG KONSENTRASI BELAJAR SISWA DI SEKOLAH - Pradini Syarifah Ramadhani (Jurnal Tata Kelola Pendidikan, 2021)
Learning concentration is one of the important thing in student learning success. Concentration is needed to understand the material delivered by the teacher. One factor that supports concentrate is breakfast. Although it’s often ignored or underestimated, but actually it the main support of the brain to improve concentration of learning. Skipping breakfast can cause lethargy, weakness, dizziness and drowsiness. It causes a decrease or difficulty in concentrating during school learning activities. So breakfast is needed because it can improve concentration of learning.